(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research is dedicated to the study of the different dimensions and constructs of the contemporary ceramic murals in the Kurdistan Region، which consists of four parts، the first part is the topics related to the introductory part of the research. Each of the research problems، importance of research، research goals، and research boundaries is presented. The short-term problem of the research based on these assumptions 1-Are the different dimensions and constructs of the contemporary ceramic murals in the Kurdistan Region working with the kurdish artists? 2- Is the ability of contemporary ceramic murals in the Kurdistan Region compared to the world’s mural products in terms of aesthetic thought show the appearance of art? With the aim of introducing the different and constructive dimensions of contemporary ceramic murals in the Kurdistan Region. Chapter two is the framework of the research theory، which discusses the history of the emergence of ceramic mural art in the civilization of Mesopotamia and ancient Egypt، and the art of ceramic murals in the Islamic world as well as the techniques and styles of contemporary ceramic murals. The third chapter of the researchers took samples of the artworks of artists from the Kurdistan Region who worked on ceramic murals، presented in scientific methods and methods. Chapter four discusses the results، conclusions، recommendations and references.